1998
DOI: 10.1088/0022-3727/31/2/011
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the applicability of perturbation techniques to solve the boundary integral equations for a parallel-plate capacitor with a rough electrode

Abstract: We derive a system of integral equations for the surface charge distribution on the electrodes of a parallel-plate capacitor for which the profile of one electrode is rough. We show that the solution to this system of equations is tractable using a perturbation technique assuming small surface heights compared with the mean plate separation. The accuracies of the first- and second-order perturbative approximations and of the local height approximation are evaluated for a few examples with a one-dimensional rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…We present the values of the normalized capacitance per unit length, C, which corresponds to the ratio of the capacitance due to the central section of length L (see figure 1), which coincides with an integer number of periods The local-height (LH) approximation [1] to the normalized capacitance per unit length for the central half of the surface is calculated using the local separation between the plates at each value of x:…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…We present the values of the normalized capacitance per unit length, C, which corresponds to the ratio of the capacitance due to the central section of length L (see figure 1), which coincides with an integer number of periods The local-height (LH) approximation [1] to the normalized capacitance per unit length for the central half of the surface is calculated using the local separation between the plates at each value of x:…”
Section: Theorymentioning
confidence: 99%
“…In previous papers [1,2] we investigated the problem of the capacitance of a capacitor with one plane surface and one rough (about a mean plane) surface. We showed that a perturbative solution was valid in a wider range of parameters of the rough surface than a simple 'local-height' solution and that it is possible to find approximate equations which fit the capacitance values over a wide range of parameter values and surface shapes for the rough surface.…”
Section: Introductionmentioning
confidence: 99%
“…When surface topography on the electrodes is taken into account, analysing the capacitance and electric field becomes a non-trivial undertaking which requires cumbersome numerical calculations [18,19] or approximate analytical solutions by considering limit cases of the surface topography [14][15][16][17]. A common approach taken with problems involving rough surfaces is to replace the original rough surfaces with an equivalent rough surface and a flat [25].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It has been shown that roughness has an adverse effect on a variety of electrical characteristics of those devices including conductivity of semiconducting and metallic thin films [11], gate oxide leakage currents in metal-oxide-semiconductor devices [12], and dielectric breakdown of triple-layer films used in dynamic random access memories [13]. Moreover, it has been shown that the capacitance, electric field and leakage currents [14][15][16][17][18][19] of microelectronic capacitors are affected by surface topography on the electrodes. These findings imply a possible influence of surface topography on the electromechanical characteristics of parallel-plate MEMS capacitors, which has not been studied thoroughly yet.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9]. The frequency response of rough interface depends on the regime under consideration such as for example (i) the capacitive behavior of rough electrodes [24][25][26][27][28][29][30][31][32][33][34][35][36], and (ii) diffusion controlled charge transfer on rough interfaces [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%